Modelo de calidad para la evaluación de herramientas case. Adaptado al estándar internacional ISO/IEC 14102. Caso de estudio (Publicaciones en Ciencias y Tecnología, 2009)
A main objective of software engineering is to produce high quality software, in this report we applied a quality model that is one of the most delicate fields in systems development such as CASE tools, as we know CASE tools are a software product used to support almost all a activities involved in the analysis, design and software construction. A description of quality model allows the evaluation and selection of CASE tools; this model used as main resources Rojas and Pérez Technological Indicators and ISO/IEC 14102 standars, in addition we detailed results of the application to a studied case.
Keywords: CASE; Quality; ISO/IEC 14102; Evaluation; Standards